Kinerja Diskominfotiksan Kota Pekanbaru dalam Menyampaikan Informasi terkait Bantuan Sosial Covid-19 - Harapan Tua Ricky Freddy S; Novrida Wulandari (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2021)
Economy is one of the things that have an impact due to Covid-19 pandemic. This has caused not a few people to experience layoffs due to the impact of the Covid-19 pandemic. The solution to this problem by supporting and assisting the affected communities to rebuild. Therefore, the government provides various types of assistance that are presented during this pandemic. The Pekanbaru City Communication, Informatics, Statistics, and Encryption Service has a role in conveying information related to city government, including disseminating information regarding Covid-19 social assistance to public. Information related to social assistance during this pandemic is very much needed for affected communities. Therefore, this study aims to find out how performance of the Pekanbaru City Communication, Informatics, Statistics, and Encoding Office in conveying information related to Covid-19 social assistance and what factors are supporting the performance of the Pekanbaru City Communication, Information, Statistics, and Encryption Service. in conveying information. The theoretical concept used in this research is the performance measurement indicator by Agus Dwiyanto (2006). The research method used is a qualitative research method with a descriptive approach through interviews, observation, and documentation. The results of this study are that the performance of the Pekanbaru City Communication, Informatics, Statistics, and Encoding Office is good and skilled but needs to improve coordination with each OPD so that the delivery of information related to COVID-19 social assistance becomes clearer and the factors that affect the performance of the office are the ability of employees, work motivation, work environment, networking, and coordination.